2015
DOI: 10.1080/10382046.2015.1086105
|View full text |Cite
|
Sign up to set email alerts
|

In school we have not time for the future: voices of Swedish upper secondary school students about solidarity and the future

Abstract: The present article presents results obtained from a survey focusing on attitudes to solidarity among upper secondary school students. A relation between positive attitudes to solidarity and future-orientation was evident. The survey results were reinforced by a second study, exploring how students in the Swedish upper secondary school perceived the value solidarity, and whether the future-dimension was reflected in teaching. Twenty-two third-year students attending theoretical and vocational programmes at fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
(35 reference statements)
1
6
0
1
Order By: Relevance
“…Thus, according to researchers and experts, the future and the complexity connected to it ought to be an important part of ESD. Torbjörnsson and Molin (2015) have shown, however, that future dimensions are not a common topic in schools, at least not in Swedish schools, when students are asked if they have learned about the future (see also Hicks, 2002). In addition, many studies performed in different countries indicate that people are quite pessimistic about the global future, particularly when it comes to environmental problems such as climate change (Connell et al 1999;Hicks, 2002;Nordensvaard, 2014;Strife, 2012;Threadgold, 2012;Tucci et al, 2007).…”
Section: Future Dimensions In Esdmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, according to researchers and experts, the future and the complexity connected to it ought to be an important part of ESD. Torbjörnsson and Molin (2015) have shown, however, that future dimensions are not a common topic in schools, at least not in Swedish schools, when students are asked if they have learned about the future (see also Hicks, 2002). In addition, many studies performed in different countries indicate that people are quite pessimistic about the global future, particularly when it comes to environmental problems such as climate change (Connell et al 1999;Hicks, 2002;Nordensvaard, 2014;Strife, 2012;Threadgold, 2012;Tucci et al, 2007).…”
Section: Future Dimensions In Esdmentioning
confidence: 99%
“…How then do young people perceive the global future-do they feel hope because of utopian collective visions? What studies have shown is that many young people have either a very bleak picture of the global future (Hicks, 1996(Hicks, , 2002Threadgold, 2012), or they have underdeveloped views of it (Torbjörnsson & Molin, 2015). If they have positive views, they are mainly based on techno-optimistic visions where new technological innovations will solve the climate problem (Byrne, Ideland, Malmberg, & Gracea, 2014;Fløttum, Dahl, & Rivenes, 2016;Pettersson, 2011).…”
Section: Utopian Goal-oriented Hopementioning
confidence: 99%
“…Thomas Torbjornsson and Lena Molin [15],about exploring solidarity attitudes among high school students in Sweden in 2015, involved twenty-two third-year students. The results of the research show that students do not recognize solidarity because the concept and case history of solidarity have never been raised in the class.…”
Section: A Relevantstudiesmentioning
confidence: 99%
“…The author examines junior high school students and examines the mentoring strategies of the learning community in forming solidarity among students.5. Zhang and Chen [16] analyzed ethnic solidarity education in China in 2014. The result of this research is that the practice of solidarity education in China bears a resemblance to western multicultural education, however, it remains to have a unique characteristic of authentic Chinese education.…”
Section: A Relevant Studiesmentioning
confidence: 99%